Clinical outcomes of low‐dose pharmacokinetic‐guided extended half‐life versus low‐dose standard half‐life factor VIII concentrate prophylaxis in haemophilia A patients - Rakmanotham, Arunothai; Moonla, Chatphatai; Sosothikul, Darintr (Haemophilia : the official journal of the World Federation of Hemophilia, 2023)
Introduction Despite receiving standard half‐life (SHL) factor VIII (FVIII) concentrates prophylaxis, some severe haemophilia A (HA) patients still encounter spontaneous breakthrough bleeding. Individualized pharmacokinetic (PK)‐guided dosing of extended half‐life (EHL) FVIII concentrates may reduce their bleeding events. Aim To compare clinical outcomes before and after switching low‐dose prophylaxis using weight‐based SHL FVIII to PK‐guided EHL FVIII concentrates, taking into consideration of a trough FVIII activity at 1 IU/dl above natural baseline. Methods In this single‐centre prospective cohort, Thai severe or moderate HA (FVIII activity ≤3 IU/dl) patients receiving low‐dose weight‐based SHL FVIII prophylaxis were enrolled. After a 3‐day wash‐out period, participants underwent low‐dose EHL FVIII prophylaxis with PK‐based adjustment (myPKFiT®) for 6 months. The annualized bleeding rates (ABR), the annualized joint bleeding rates (AJBR), the haemophilia‐specific quality‐of‐life (Haemo‐QoL or Haemo‐QoL‐A) scores, the Hemophilia Joint Health Scores (HJHS) and the annualized FVIII consumption were compared between the two prophylactic periods. Results Of 15 eligible subjects (mean age 18.7 ± 6.7 years), ABR, AJBR and HJHS were significantly reduced (mean differences of ‐11.1 ± 4.9 bleeds/year, ‐10.4 ± 5.2 joint bleeds/year and ‐5.1 ± 1.5 marks, respectively; P < .001 for all comparisons) after switching regimen. The quality‐of‐life scores had also improved (P = .001). Nonetheless, FVIII consumption tended to increase despite no statistical significance (means of 1240.9 ± 531.3 SHL FVIII IU/kg/year versus 1591.7 ± 438.9 EHL FVIII IU/kg/year; P = .05). Conclusions This is the first low‐dose, PK‐guided, EHL FVIII prophylaxis clinical study in Thailand. Benefits and practicability of this personalized regimen may support the implementation of regular FVIII prophylaxis in developing countries with budget constraints. ClinicalTrials.gov NCT05281185.